Risk Analysis of Cargos Damages for Aquatic Products of Refrigerated Containers: Shipping Operators’ Perspective in Taiwan - Tseng, Wen-Jui; ., Chien-Chang Chou; ., Fu-Ting Hsu; ., Yu-Meng Wang; ., Ya-Ning Liu, Nai-Wen Chang, Yi-Wen Wu (Information Management and Business Review, 2012)
As the development of refrigerated container, transportation of aquatic products is growing rapidly in recent years. It is very important to avoid cargos damages for aquatic products of refrigerated containers, while the shipping operators are running this scope of business. Hence, the risk issue of adopting various improvement strategies would be important for the container shipping operators. In the light of this, the main purpose of this paper is to analyze the risks of cargos damages for aquatic products of refrigerated containers based on the container shipping operators’ perspective in Taiwan. We use four risk assessment procedures - risk identification, risk analysis and evaluation, risk strategies, and risk treatment - as the research method in this paper. The risk factors are generated from literature review and experts interviewing. Then, three dimensions with nineteen risk factors are preliminary identified. We used these risk factors to proceed with the empirical study via questionnaires. Three points of empirical results are presented. At first, the top factor of perceived risk as well as of risk severity is ‘container data setting errors.’ Secondly, the top factor of risk frequency is ‘lack of the goods’ pre-cooling themselves.’ Thirdly, three risk factors are classified into the low-risk area, whereas sixteen risk factors are placed on the medium-risk area. There is no risk factor fix on the high-risk area. Furthermore, three risk strategies - risk prevention, risk reduction, and risk transfer - are suggested to adopt by different risk factors.